2020
DOI: 10.1111/nmo.13783
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of self‐reported painful and non‐painful constipation in the general population

Abstract: Introduction Chronic constipation, defined by the Rome IV criteria, is a highly prevalent functional bowel disorder with major overlap with other bowel disorders. Therefore, a pooled‐analysis to evaluate the presence of self‐reported constipation in the general population was conducted. Further, its association with other bowel symptoms and its health‐economic impact was analyzed. Methods Collection of information on bowel symptoms’ prevalence and their impact was done through an Internet survey (Medistrat Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Likewise, with regard to patients, a significant number informed a duration of symptoms greater than 20 years. This fact infers the greater reliability and precision in obtaining information and emphasizes the chronic nature of intestinal constipation 1 , 4 , 16 , 23 , 28 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Likewise, with regard to patients, a significant number informed a duration of symptoms greater than 20 years. This fact infers the greater reliability and precision in obtaining information and emphasizes the chronic nature of intestinal constipation 1 , 4 , 16 , 23 , 28 .…”
Section: Discussionmentioning
confidence: 86%
“…Intestinal chronic constipation is one of the most frequent gastrointestinal disorders in general clinical practice 17 , 27 , 28 , reaching up to 34% of the studied population. It is considered to have a high global prevalence being endemic in the elderly population and associate with a significant impact on quality of life 14 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…An OC definition is important because a large study of adults (15) found prevalence estimates of 9%–59% depending on which of 5 OC definitions was used. Prevalence rates of self-reported constipation of 21%–29.5% have been consistently reported (16–20). This contrasts with a meta-analysis of 45 studies reporting a pooled prevalence of 14% for CIC among over 261,000 adults (21).…”
Section: Introductionmentioning
confidence: 98%
“…Slow transit constipation (STC) is a kind of constipation caused by colon dynamics transportation dysfunction that slows the transmission of intestinal contents, which severely affects the quality of life of patients [1,2]. Insufficient intestinal peristalsis, abnormal intestinal nervous system and disturbance of intestinal microecological balance can all lead to STC, and the treatment of STC is mainly to relieve constipation symptoms, restore intestinal motility and defecation function [3].…”
Section: Introductionmentioning
confidence: 99%